Diferentes sustancias nutritivas en el cultivo de tomate riñón (Lycopersicum sculentum) en sustrato de cascarilla de café más arena de río - Castillo Zambrano, Andrés Alfonso (2015)
This research entitled "Different Nutrients In Tomato Crop Kidney (Lycopersicon sculentum) in hull substrate cafe more river sand" was held at the "San Antonio" exhibition La Laguna, Canton Ventanas, Los Rios Province, whose geographical coordinates are S 1 26' 34 "W 79 ° 26'54", to a height of 73 meters. The experiment lasted 120 days. Design was used totally at random (DCA) with 4 treatments and 4 replications, to determine differences between treatment means multiple range test Duncan (P ≤ 0.05) was applied. The variables evaluated were: percentage of germination, pH measurement every 14 days, plant height every 14 days, stem diameter, days to flowering, number of fruits per plant, fruit length, fruit diameter and yield in kg per plot. Design randomized complete block compared through the Duncan test 95% probability was used. The treatment showed better results was the Evergreen (5 ml / L of water), which had the largest production and the best cost benefit ratio of 1.32 treatment, the yield per hectare was. T3 67782.83 kg.